The Effect of Perceived Product Quality and Brand Image on Purchase Decision with Trust As Mediation - Nanda Dwi Maharani; Astrid Puspaningrum; Ikhtiara Kaideni Isharina (Journal of Business and Management Review, 2023)
This research focuses on the role of Perceived Product Quality and Brand Image in increasing Purchase Decisions through Trust in consumers of skin care products from Innisfree. The purpose of this study is to explain and analyze the effect of Perceived Product Quality and Brand Image on Purchase Decisions, both directly and indirectly through Trust mediation. This type of research is explanatory research with a quantitative approach. The population in this study were consumers in Surabaya and Malang who had purchased Innisfree skin care products. Data was collected by distributing questionnaires to 150 respondents who met the criteria. Data analysis used Structural Equation Modeling Partial Least Squares (SEM-PLS) with SmartPLS software. The results of the study show that Perceived Product Quality and Brand Image have a significant effect on Purchase Decision. Likewise, Trust has a significant influence on Purchase Decision. The results also show that Trust partially mediates the effect of Perceived Product Quality and Brand Image on Purchase Decisions